Desiccant cooling systems: a review - Sahlot, Minaal; Riffat, Saffa (Oxford University Press, 2016)
Desiccant cooling systems have been considered as an efficient method of controlling moisture content in supply air. They do not use any ozone-depleting coolants and consume less energy as compared with the vapour compression systems. This communication provides an extensive review of liquid desiccant systems (LDSs). All the components of an LDS such as dehumidifier, regenerator, packing material and liquid desiccant properties along with its energy storage capabilities have been discussed in detail. In addition, hybrid of LDSs with sensible cooling technologies has been studied. Various types of mathematical models to predict the outlet parameters of the desiccant system and current issues in liquid desiccants have been reviewed in detail. Moreover, solid and other advanced desiccants have also been discussed briefly. Finally, a summary of some successful case studies and economic evaluation of desiccant systems have been given.